PENEGAKAN HUKUM DALAM PENANGANAN TINDAK PIDANA PENGGELAPAN - Nurbaiti Syarif (Fakultas Hukum Universitas Tulang Bawang, 2020)
Embezzlement in the Criminal Code is classified as a crime. The embezzlement is contained in Article 372 of the Criminal Code. The focus of this research is law enforcement in dealing with criminal acts of embezzlement and the inhibiting factors of law enforcement in handling embezzlement. Based on the results of research and discussion, it shows that law enforcement in handling embezzlement is carried out using non-penal and penal methods. The non-penal approach is carried out by providing counseling and socialization in the context of fostering social responsibility for citizens of the crime of embezzlement. Legal counseling is particularly carried out in areas prone to criminal acts. The criminal approach is carried out through legal measures so that the perpetrators of the criminal act of embezzlement are processed legally in order to obtain criminal sanctions and guarantee legal certainty. Inhibiting factors for law enforcement in handling criminal acts of embezzlement include: criminal sanctions in Article 372 of the Criminal Code have not provided a deterrent effect, limitations on law enforcement agencies, limited state special budget for law enforcement, lack of public awareness of the importance of understanding crime, society becomes a criminal act. Keywords : Law Enforcement, Crime, Embezzlement.